Attributes characterizing spontaneous ultra-weak photon signals of human subjects - Bajpai, Rajendra P.; Van Wijk, Eduard P.A.; Van Wijk, Roeland; van der Greef, Jan (Journal of photochemistry and photobiology. B, Biology, 2013)
•Focus on human weak photon emission from two symmetric body locations.•Finding procedures to develop attributes that quantify the photon signals.•The shift from the parameter “Intensity” to analysis of photon count distribution.•To include time aspects into photon count distribution analysis.•To include additionally the body’s symmetry of the signal. Sixty visible range photon signals spontaneously emitted from the dorsal side of both hands of fifteen human subjects are analyzed with the aim of finding their attributes. The signals are of 30min duration and detected in bins of 50ms by two synchronized photo multipliers sensitive in the range (290–630nm). Each signal is a time series of 36,000 elements. The attributes of its signal are determined from the statistical properties of time series. The mean and variance of time series determine the attributes signal strength and intercept (p0) and slope (p1) of the Fano Factor curve. The photon count distribution of the time series determines squeezed state parameters |α|, r, θ and ϕ, squeezed state index (SSI), and sum of the squares of residue (SSR). The correlation between simultaneously detected signals determines intercept (c0) and slope (c1) of their correlation curve. The variability of attributes is studied by calculating them in smaller intervals covering the entire signal. The profile of attribute at 12 sites in a subject is more informative and biologically relevant.